Development of a Madurese Local Wisdom–Based Learning Model Using a STEAM Integrative Approach to Improve Creativity and Innovation of Indonesian Elementary School Students - Fadhilah, Mutik; Ahmad Fawaid; Ikha Yuliati; Nailatur Rahmah (UIN Sunan Kalijaga Yogyakarta, 2025)
Creativity and innovation are essential competencies for elementary school students; however, learning practices in many Indonesian elementary schools remain teacher-centered and provide limited opportunities for creative and innovative activities. In addition, local cultural values that can support contextual learning are often underutilized. Therefore, this study aims to develop a learning model grounded in Madurese local wisdom that employs STEAM as an integrative instructional approach to enhance students’ creativity and innovation at the elementary school level. This study used a research and development method with the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The effectiveness of the developed model was tested using a one-group pretest–posttest design. Data were collected through observations, interviews, questionnaires, documentation, pretest–posttest instruments, and product-based assessments. Students’ creativity was measured using Torrance indicators (fluency, flexibility, originality, and elaboration), while innovation was assessed through indicators of idea adaptation, simple implementation, usefulness, and initiative appropriate to elementary students’ developmental levels. Quantitative data were analyzed using descriptive statistics, N-Gain, and paired-sample t-tests, while qualitative data were analyzed through data reduction, display, and verification. The results indicate that the developed learning model is valid, practical, and effective. Students’ creativity increased from 57.3 to 86.6, and innovation increased from 55.8 to 84.1, with moderate-to-high N-Gain scores. The model supports contextual and culture-based learning by strengthening creativity, innovation, and STEAM-related competencies while preserving Madurese local wisdom.